A Review of User-Centered Design for Diabetes-Related Consumer Health Informatics Technologies. (July 2013) - LeRouge, Cynthia; Wickramasinghe, Nilmini
User-centered design (UCD) is well recognized as an effective human factor engineering strategy for designing ease of use in the total customer experience with products and information technology that has been applied specifically to health care information technology systems. We conducted a literature review to analyze the current research regarding the use of UCD methods and principles to support the development or evaluation of diabetes-related consumer health informatics technology (CHIT) initiatives. Findings indicate that (1) UCD activities have been applied across the technology development life cycle stages, (2) there are benefits to incorporating UCD to better inform CHIT development in this area, and (3) the degree of adoption of the UCD process is quite uneven across diabetes CHIT studies. In addition, few to no studies report on methods used across all phases of the life cycle with process detail. To address that void, the Appendix provides an illustrative case study example of UCD techniques across development stages. Conclusion With the advancement of CHIT, such as smartphones and Web 2.0, we have the tools to provide patients with more sophisticated self-care. Given the challenges and trends in today's health care environment, CHI will inevitably expand. Given this context, designing and developing appropriate and sustainable technology solutions are important. Moreover, CHI is not just about the technology, but also and most importantly about the people (users) and context. User-centered design is concerned with users' expectations of how something should work and what it should do, how users interpret the clues that a particular device or technology provides about its functioning and content, and how users interpret feedback from the device or technology. 47 User-centered design efforts can help prevent costly design and change management errors (and associated rework). This study contributes to the existing literature by examining the use of UCD methods for CHIT related to diabetes self-management as reported in peer-reviewed publications. Results indicate that multiple UCD methods have been used to design and assess functionality related to nutrition, exercise, lifestyle, and blood glucose level self-management. These functions have been spread across various platforms. Although multimethods may be used, to our knowledge, no study within the scope of this review has demonstrated the multistage use of UCD across the UCD life cycle with a detailed accounting of process.Appendix A provides a contribution to the existing literature by addressing this gap. User-centered design activities are admittedly time-consuming. However, the referenced studies generally indicated that the UCD methods used (and thus time invested) provided positive results and/or facilitated answering their research questions. Furthermore, the time invested can be offset by post-release success and the realization that the findings, data collection tools (e.g., surveys), and resulting UCD deliverables (e.g., profiles) can be repurposed in other research and development activities involving the same or similar target user groups or contexts. At this time, one can only hypothesize the resulting impact and cost/benefit if methods across all stages of the UCD life cycle are incorporated into studies or what the optimal mix of methods is to suit the purpose of the study. This situation provides an opportunity for future research. However, UCD is not a silver bullet for universal system success. Although development efforts may take into account consumer input and produce positive design and functionality outcomes, CHIT may not be for everyone. Appropriate CHIT "fit" to a situation or user may be dictated by not only by alignment with the user's mental model, but also costs, whether the consumer owns a computer, Internet access, and self-motivation. In summary, our review of the literature strongly supports that incorporating UCD methods with appropriate rigor and choice of methods not only is prudent, but also facilitates true and faithful capture and delivery of what is quintessentially important within the domain of CHI—the users' mental model.